Clinical features and characteristics of retinopathy of prematurity in developing countries - Dogra, Mangat R.; Katoch, Deeksha (Annals of Eye Science; Vol 3 (January 2018): Annals of Eye Science, 2018)
Retinopathy of prematurity (ROP) is an emerging cause of childhood blindness in the developing countries. The low and middle-income countries are facing common challenges in the midst of the ‘third epidemic’ of ROP. Improvement in neonatal care facilities has increased survival of preterm babies. Lack of awareness and non-uniform standards of care in the ever-increasing number of neonatal intensive care units (NICUs) and special newborn care units (SNCUs) has resulted in this surge of ROP. Apart from low birth weight and the degree of prematurity, use of unblended supplemental oxygen, sepsis, anemia and blood transfusion are important risk factors associated with ROP in developing countries. Atypical forms of aggressive posterior ROP (APROP) are seen in heavier birth weight babies in the developing countries. Prevention of ROP by good quality neonatal care, timely diagnosis by mandatory ROP screening in NICUs and training manpower for laser treatment of ROP requires close collaboration between the neonatologists, ophthalmologists and the policy makers. Team approach and inter-disciplinary co-ordination are keys in a nation’s drive to fight this preventable cause of blindness.